A second-hand clothing application with recommendation and personal wardrobe management - Wan, Yi Mun (2024)
Currently, the market is dominated in more general used second-hand application and few used second-hand clothing related applications. Therefore, this proposal is related to the development of a second-hand clothing application that is designed to enhance the user experience and improve the problems of existing applications. The project is to solve the problems of the existing application, such as the insufficient personal wardrobe management systems, lack of tool for providing outfit recommendation tools and insufficient trust in second-hand e-commerce transactions. These limitations are determined through the reading of the journal article, testing and review of the existing application in the market and the data from the survey. To solve this limitation, some comprehensive features such as a personal wardrobe management system with outfit planning that can also link with second-hand item market, outfit recommendation driven by generative ai, personalized recommendations based on their personal preferences will be included. In addition, the meet-up features will also be included that ensure buyers and sellers can have a more secure and convenient transactions. The methodology that was employed to develop this project is a hybrid methodology, which includes the agile and waterfall approaches. The tool that was used to develop this project is React Native with integrates Firebase as the storage for the information in this application.